Expression of Ki-67 and E-cadherin in patients with non-small cell lung cancer attending a tertiary care hospital - Farzana Afroze; Latifa Nishat; Farida Arjuman; Zinnat Ara Yesmin; Lutfun Nahar; Rokhsana Tanjin (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: E-cadherin and Ki-67 expressions may provide real-time insights into the tumor's status and can be utilized as targeted therapeutics for lung cancer. We aimed to explore the expression of Ki-67 and E-cadherin in non-small cell lung cancer (NSCLC) patients and to identify their association with clinicopathological features.